1998
DOI: 10.3171/foc.1998.4.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary neurological tumor syndromes: clues to glioma oncogenesis?

Abstract: The author reviewed five hereditary neurological tumor syndromes associated with gliomas: Li-Fraumeni cancer syndrome, neurofibromatosis type 1 (NF1) and type 2 (NF2), tuberous sclerosis (TS), and Turcot syndrome. In each case, clinical manifestation, genetic localization, and protein function were identified. Correlation with glioma oncogenesis demonstrated the following associations: 1) p53 mutation (Li-Fraumeni) with astrocytoma progression; 2) NF1 mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…These findings indicated that the malignant phenotype of astrocytomas is at least partially regulated by β-catenin signaling and that the molecular mechanisms underlying the activation of astrocytes are closely related to the mechanisms of pathogenesis and the progression of growth of astrocytomas. Patients with Turcot syndrome highlight the involvement of β-catenin signaling in tumorigenesis within the CNS, where mutations of the APC gene, an important regulator of β-catenin signaling, cause the formation of brain tumors (29).…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicated that the malignant phenotype of astrocytomas is at least partially regulated by β-catenin signaling and that the molecular mechanisms underlying the activation of astrocytes are closely related to the mechanisms of pathogenesis and the progression of growth of astrocytomas. Patients with Turcot syndrome highlight the involvement of β-catenin signaling in tumorigenesis within the CNS, where mutations of the APC gene, an important regulator of β-catenin signaling, cause the formation of brain tumors (29).…”
Section: Discussionmentioning
confidence: 99%
“…Prior experience with submucosal tunneling [8] and peroral endoscopic myotomy (POEM) has suggested safety of such an approach [11, 12]. Access strategies for surgical interventions in the thoracic spine most commonly include thoracotomy, costovertebral, posterolateral, and transpedicular percutaneous approaches [1316]. Open surgical techniques to expose the spine require the separation of musculoskeletal structures and traction of nerve roots to create an access large enough to accommodate surgical tools.…”
Section: Discussionmentioning
confidence: 99%
“…Neurofibromatosis type 1 (NF-1), von Hippel-Lindau disease, tuberous sclerosis, Li-Fraumeni and Turcot's neoplasia syndrome patients have an increased incidence of brain tumors, including brainstem neoplasms (Chen 1998;Albers & Gutmann 2009;Farrell & Plotkin 2009). Neurofibromatosis type 1 (NF-1), von Hippel-Lindau disease, tuberous sclerosis, Li-Fraumeni and Turcot's neoplasia syndrome patients have an increased incidence of brain tumors, including brainstem neoplasms (Chen 1998;Albers & Gutmann 2009;Farrell & Plotkin 2009).…”
Section: Etiologymentioning
confidence: 99%